2018
DOI: 10.1080/20008198.2018.1512264
|View full text |Cite
|
Sign up to set email alerts
|

Testing the ICD-11 proposal for complex PTSD in trauma-exposed adults: factor structure and symptom profiles

Abstract: Background: The proposed ICD-11 criteria for trauma-related disorders define posttraumatic stress disorder (PTSD) and complex posttraumatic stress disorder (cPTSD) as separate disorders. Results of previous studies support the validity of this concept. However, due to limitations of existing studies (e.g. homogeneity of the samples), the present study aimed to test the construct validity and factor structure of cPTSD and its distinction from PTSD using a heterogeneous trauma-exposed sample. Method: Confirmator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…The distinction between two latent classes of participants with high PTSD scores, one scoring high only on PTSD symptoms, the other scoring high on both PTSD and DSO-symptoms, maps onto the ICD-11 specification of CPTSD and replicates findings from previous studies (Böttche et al, 2018;Cloitre et al, 2013Cloitre et al, , 2014Elklit et al, 2014;Karatzias et al, 2018Karatzias et al, , 2017Kazlauskas et al, 2018;Knefel et al, 2015;Murphy et al, 2016;Palic et al, 2016;Sachser et al, 2017). Consistent with the ICD-11 model of CPTSD, childhood interpersonal trauma was a statistically significant predictor of CPTSD, as compared to PTSD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The distinction between two latent classes of participants with high PTSD scores, one scoring high only on PTSD symptoms, the other scoring high on both PTSD and DSO-symptoms, maps onto the ICD-11 specification of CPTSD and replicates findings from previous studies (Böttche et al, 2018;Cloitre et al, 2013Cloitre et al, , 2014Elklit et al, 2014;Karatzias et al, 2018Karatzias et al, , 2017Kazlauskas et al, 2018;Knefel et al, 2015;Murphy et al, 2016;Palic et al, 2016;Sachser et al, 2017). Consistent with the ICD-11 model of CPTSD, childhood interpersonal trauma was a statistically significant predictor of CPTSD, as compared to PTSD.…”
Section: Discussionsupporting
confidence: 82%
“…The ICD-11 model of CPTSD has been tested in several studies, usually using mixture models, such as latent class analysis and latent profile analysis (LPA), which identify different homogenous sub-populations that share similar patterns of symptom endorsement (Nylund, Asparouhov, & Muthén, 2007). To the best of our knowledge, 12 mixture model studies on ICD-11 PTSD and CPTSD have been published to date (Böttche et al, 2018;Cloitre, Garvert, Brewin, Bryant, & Maercker, 2013;Cloitre, Garvert, Weiss, Carlson, & Bryant, 2014;Elklit, Hyland, & Shevlin, 2014;Karatzias, Hyland, Ben-Ezra, & Shevlin, 2018;Karatzias et al, 2017;Kazlauskas, Gegieckaite, Hyland, Zelviene, & Cloitre, 2018;Knefel, Garvert, Cloitre, & Lueger-Schuster, 2015;Murphy, Elklit, Dokkedahl, & Shevlin, 2016;Palic et al, 2016;Sachser, Keller, & Goldbeck, 2017;Wolf et al, 2015). All except one (Wolf et al, 2015), previous studies identified the presence of at least two distinct symptom profiles; one describing a group of individuals reporting high levels of CPTSD symptoms in both PTSD and DSO-symptom clusters, another endorsing high levels of PTSD symptoms only.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using archival data reported similar findings (e.g. Böttche et al, 2018 ; Shevlin et al, 2017 ). Taken together, the symptom structure of ICD-11 CPTSD seems to be best reflected in a two-factor higher-order model or a correlated six-factor model, evidencing the need for additional studies in different samples using precise descriptions of ICD-11 symptom content.…”
Section: Introductionsupporting
confidence: 55%
“…These were identified from a scoping review of assessment tools currently used in the perinatal period (Chamberlain et al, 2019b), and from consultation with leaders in the field. Information about the assessment tools were collated, with items mapped onto existing trauma symptom clusters (American Psychiatric Association [APA], 2013; Cloitre et al, 2014;Böttche et al, 2018;World Health Organisation [WHO], 2018), and additional Aboriginal cultural idioms of distress (Atkinson, 2008). The working group members determined that a domain regarding 'recognition' of parents who may be at higher risk of experiencing symptoms of complex trauma (e.g., a history of childhood abuse) (coded as '0') and 11 'areas of distress' should be taken forward for discussion with key stakeholders at the second key co-design workshop ( Table 1).…”
Section: Identifying and Synthesizing Existing Complex Trauma Assessmmentioning
confidence: 99%